A Fully‐Integrated Penta‐Band Tx Reconfigurable Power Amplifier with SOI CMOS Switches for Mobile Handset Applications. Issue 2 (1st April 2014) - Kim, Unha; Kang, Sungyoon; Kim, Junghyun; Kwon, Youngwoo
Abstract : A fully‐integrated penta‐band reconfigurable power amplifier (PA) is developed for handset Tx applications. The output structure of the proposed PA is composed of the fixed output matching network, power and frequency reconfigurable networks, and post‐PA distribution switches. In this work, a new reconfiguration technique is proposed for a specific band requiring power and frequency reconfiguration simultaneously. The design parameters for the proposed reconfiguration are newly derived and applied to the PA. To reduce the module size, the switches of reconfigurable output networks and post‐PA switches are integrated into a single IC using a 0.18 μm silicon‐on‐insulator CMOS process, and a compact size of 5 mm × 5 mm is thus achieved. The fabricated W‐CDMA PA module shows adjacent channel leakage ratios better than −39 dBc up to the rated linear power and power‐added efficiencies of higher than around 38% at the maximum linear output power over all the bands. Efficiency degradation is limited to 2.5% to 3% compared to the single‐band reference PA.